Art and design workshops at a residential care facility - social care professionals' experiences of co-creation and participation in designing the physical environment - Ewa Wikström; Synneve Dahlin-Ivanoff; Maja Gunn; Qarin Lood (BMC, 2024)
Abstract Background Co-creation and participation among different user groups have been highlighted as pivotal for improving residential care facilities for older persons. However, more knowledge is needed on methods aiming to overcome challenges in constructing inclusive co-creation and participation processes. In particular, there is a need for knowledge concerning how art and design workshops could contribute to co-creation and participation of social care professionals designing the physical environment in residential care facilities. Therefore, this study aimed to examine how art and design workshops can contribute to co-creation and participation in designing the physical environment with residential care facility professionals. Methods A qualitative method was used to investigate social care professionals' experiences. Data were collected through semi-structured group interviews and analysed with inspiration from Corbin and Strauss's analysis method. Results This study concludes that art and design workshops could serve as deliberating and developing practices. First, the art and design workshop as a deliberating practice involves conditions that create a communication arena and space supporting professionals in sharing experiences and voicing different perspectives. Second, the art and design workshop, as a developing practice, supports shared agency through dialogue focusing on designing the physical environment in residential care facilities, using photographs, materials, and fabrics. Conclusions This research contributes to the understanding of the relevance of art and design workshops and co-creation between artists and social care professionals in designing the physical environment in residential care facilities. The study can be valuable in identifying important mechanisms that facilitate co-creation and participation among social care professionals, as well as the development of art and design as a tool for improving environments in residential care facilities. The research focuses on how art and design workshops could influence co-creation and participation through art and design from the perspective of social care professionals.